2014
DOI: 10.1038/nchembio.1497
|View full text |Cite
|
Sign up to set email alerts
|

Lysine 2-hydroxyisobutyrylation is a widely distributed active histone mark

Abstract: We report the identification of a new type of histone mark, lysine 2-hydroxyisobutyrylation (Khib), and identify the mark at 63 human and mouse histone Khib sites, including 27 unique lysine sites that are not known to be modified by lysine acetylation (Kac) and lysine crotonylation (Kcr). This histone mark was initially identified by MS and then validated by chemical and biochemical methods. Histone Khib shows distinct genomic distributions from histone Kac or histone Kcr during male germ cell differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
410
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(426 citation statements)
references
References 29 publications
6
410
0
1
Order By: Relevance
“…shermanii (PfMCM) (13,14). These studies showed that binding of the acyl-CoA substrate results in a large conformational change that causes the formation of an initial radical by homolysis of the adenosylcobalamin-cobalt bond in the coenzyme B 12 . This 5Ј-deoxyadenosyl radical abstracts a hydrogen atom from the substrate (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…shermanii (PfMCM) (13,14). These studies showed that binding of the acyl-CoA substrate results in a large conformational change that causes the formation of an initial radical by homolysis of the adenosylcobalamin-cobalt bond in the coenzyme B 12 . This 5Ј-deoxyadenosyl radical abstracts a hydrogen atom from the substrate (Fig.…”
mentioning
confidence: 99%
“…Coenzyme B 12 -dependent acyl-CoA mutases are a relatively small family of enzymes catalyzing carbon skeleton rearrangements through a unique radical mechanism (1). Thus far, methylmalonyl-CoA mutase (MCM), 5 ethylmalonyl-CoA mutase (ECM), and isobutyryl-CoA mutase (ICM) have been characterized (2)(3)(4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Histones are easily catalyzed by histone modification enzymes to form different kinds of posttranslational modifications, such as methylation, acetylation and phosphorylation (Campos and Reinberg, 2009;Kouzarides, 2007). Until now, more than a dozen types of histone modifications and hundreds of modification sites altogether have been found (Arnaudo and Garcia, 2013;Dai et al, 2014;Kouzarides, 2007;Tan et al, 2011) (Figure 1). …”
Section: Introductionmentioning
confidence: 99%
“…While DNA is affected by methylation and derived chemical modifications of cytosine residues, histone proteins are subject to a variety of post-translational modifications that include, but are not limited to, methylation of lysines and arginines, phosphorylation of serine and tyrosine residues, acetylation, crotonylation and butyrylation as well as ubiquitination of lysines. An extensive overview of the chemistry and effective role in chromatin regulation for these and other modifications can be found in recently published works and reviews by different research groups (Tan et al, 2011;Dai et al, 2014;Tessarz & Kouzarides, 2014;Bowman & Poirier, 2015;McGinty & Tan, 2015). Despite their different nature and effect, all these modifications are installed, recognized or removed by dynamic processes, which affect and control chromatin accessibility, gene regulation and activity, as well as the repair of damaged DNA, key to maintaining genome stability.…”
Section: Introductionmentioning
confidence: 99%